Bond pricing and the macroeconomy - Gregory R. Duffee (The Johns Hopkins University, Department of Economics, 2012)
This chapter reviews some of the academic literature that links nominal and real term structures with the macroeconomy. The main conclusion is that none of our models is consistent with basic properties of nominal yields. It is difficult to explain the average shape of the nominal yield curve, the variation of yields over time, and the predictability of excess bond returns. There are two overarching problems. First, much of the variation over time in economic activity is orthogonal to variation in nominal yields, and vice versa. Second, although mean excess returns to nominal Treasury bonds are positive, these returns do not appear to positively covary with risks that require compensation, at least according to standard asset-pricing models.
Keywords: G12; 330; Term structure; affine models; macro-finance; no-arbitrage; Anleihe; Zinsstruktur; Risikoprämie; Arbitrage Pricing; USA